Spatial representations and policy implications of industrial co-agglomerations, a case study of Beijing. (July 2016) - Yang, Zhenshan; Song, Tao; Chahine, Teresa
Abstract: Industrial parks have been tested in various regions around the world, in attempt to foster innovation and fuel economic growth. Despite the importance of industry co-agglomerations in regional growth, few studies examine them in regional geographic space. This paper combines exploratory spatial data analysis and input–output method to explore the spatial pattern of key industrial co-agglomerations in Beijing, which is illustrated by location, function, frequency, spatial hierarchy and spacing. The results contribute to linking abstract economic and actual geographical spaces in urban and regional growth, enabling urban and regional planners to judge and evaluate planning initiatives before and after implementation. The failure of sub-center plans and risks of industrial parks schemes in Beijing are addressed. By considering industrial input–output relations including environmental and human resources, urban planners can optimize the development of such co-agglomerations to foster sustainable urban development. Highlights: Industry co-agglomerations and their spatial representation are examined in Beijing city region. Industries are co-agglomerated significantly in some places of the region, with different ranges of distances. The co-agglomeration saturates and increases pressure in the urban center and impairs opportunity of subcenters. Associated planning failure and risks in Beijing are analyzed. This approach informs urban planning about market forces, deciphering growth from economic to geographical space.